Designing type - Cheng, Karen (Laurence King Publishing, 2020)
'Designing Type' brings insight to the art and process of developing a typeface. Illustrated with type specimens and diagrams demonstrating visual principles and letter construction, this book is useful for both experienced professionals and novice designers.
Keywords: navrhování písma; typografické písmo; type design; typefaces; příručky; handbooks and manuals